Gaston Bachelard's poetics of space: inverse dreambook for interpretation of thinking by means of building - Raičević, Andrea; Stevanovic, Vladimir (Arhitektura i urbanizam, 2020)
This paper aims to examine the philosophical work of the French epistemologist and phenomenologist – Gaston Bachelard, by transferring its interpretation from the general into a specific field of architecture. The Poetics of Space (Lа Poétique de l'Espace), as a Bachelard’s work that enjoys even today the most comprehensive reception among the architects and theorists of architecture, shall be taken as a starting point of our analysis. Intending not to limit itself to the considerations which encompass only texts that are strictly thematically or problematically dealing with architecture, this paper aims to position and contextualise Bashlar's philosophical thought within the phenomenological reflections that found their applications in the theory of architecture. In this sence, we shall provide an insight into the duality of relations between the Bachelard’s concept of poetic image (l'image poétique) and a poetic object/motif, which, in our case, referes to the inherent elements of an architectural object intended for dwelling. Therefore, in addition to the material and geometric, we shall try to apprehend and explain the experiential manner of spatial perception, and single out the echoes of Bashlar's philosophical thought, which carry within themselves a potential to distort architectural thinking. The results of research shall indirectly demonstrate two possible ways of interpreting the Bachelard’s work: 1) the analogous application and appropriation of interpretations of Bachelard’s text as a reversed manual-dreambook for provoking and inscribing the desired experience in the architectural space, and 2) the application of the mechanisms of phenomenological analysis itself, directed towards the interest in the process of creating a poetic image, as  guidelines for the actualisation of an architectural object in its specific reality, through the work on its poeticity.
Keywords: phenomenology of architecture; Gaston Bachelard; poetics of space; poetic image; spatial experience; experience of space